L’UTOPIE AU 21e SIÈCLE - Kostas Vergopoulos (Universidade Federal do Maranhão, 2016)
What can be the meaning of utopia in the XXI century? It would be different from what we had over the last two centuries? No doubt, the term Utopia indicates the desire to live in a different world, in other words, the desire for social change and therefore the category utopia means the continuing of the social change at all times. There is no reason to imagine that this desire has been able to substantially change in our century, compared to what was in the course of previous centuries. However, the concept of Utopia, distinguished its generic content that does not change, on one hand; and on the other, the means to achieve it , they can certainly change with the seasons. Although the desire for a different world has always been so intense, the means and the ways to achieve it were not always the same.